Praktik Pendidikan Agama Islam Berbasis Penguatan Karakter Religius dan Jujur di Lingkungan Full Day School: Studi Kasus di SD Plus Tahfizhul Quran (PTQ) Annida Salatiga - Mulyani Setyaningsih; Ahmad Fikri Sabiq (research, training and philanthropy institution Natural Aceh, 2021)
Abstract: The purpose of this study is to determine the implementation of Islamic education based on religious and honest character in full day school. This research is a field research with a qualitative approach. The data collection techniques are interview, observation, and documentation. This research is located at SD Plus Tahfizhul Quran (PTQ) Annida Salatiga and the respondens are the principal, teachers, and parents of students. The analysis in this research is descriptive. The policy of strengthening the religious character and honest attitude of SD PTQ Annida Salatiga students is planned in a structured manner through planning programs and work programs. Religious and honest character is by carrying out the values ​​contained in religious characters such as praying, praying, reading the Al-Qur'an and fasting. Strengthening the character of an honest attitude, namely muroja'ah book reports, children's prayer book reports, honesty not bringing pocket money, and pickets according to schedule. Implementation of this honest and religious character education program through intracurricular, co-curricular and extracurricular activities. These character education programs have positive results as same with parents' expectations Abstrak: Penelitian ini bertujuan untuk mengetahui praktik pendidikan agama Islam berbasis penguatan karakter religius dan jujur di lingkungan full day school. Penelitian ini merupakan penelitian lapangan dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan peneliti adalah wawancara, observasi, dan dokumentasi. Penelitian ini berlokasi di SD Plus Tahfizhul Quran (PTQ) Annida Salatiga dengan narasumber adalah kepala sekolah, guru, dan orang tua siswa. Analisis dalam penelitian ini adalah deskriptif. Kebijakan penguatan karakter religius dan sikap jujur siswa SD PTQ Annida Salatiga direncanakan secara terstruktur melalui program perencanaan dan program kerja. Penguatan karakter religius dan jujur adalah dengan melaksanakan nilai-nilai yang terkandung dalam karakter religius seperti berdoa, ibadah sholat, membaca Al-Qur’an dan ibadah puasa. Penguatan karakter sikap jujur yaitu laporan buku muroja’ah, laporan buku sholat anak, kejujuran tidak membawa uang saku, dan piket sesuai jadwal. Pelaksaan program penguatan karakter religius dan jujur ini melalui kegiatan intrakurikuler, kokurikuler dan ekstrakurikuler. Program-program penguatan karakter ini memiliki hasil positif sesuai harapan orang tua.